2017
DOI: 10.3390/molecules22050767
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for the Preparative Isolation and Purification of Flavonoids from Leaves of Crataegus pinnatifida by HSCCC and Pre-HPLC

Abstract: In this work, flavonoid fraction from the leaves of Crataegus pinnatifida was separated into its seven main constituents using a combination of HSCCC coupled with pre-HPLC. In the first step, the total flavonoid extract was subjected to HSCCC with a two-solvent system of chloroform/methanol/water/n-butanol (4:3:2:1.5, v/v), yielding four pure compounds, namely (–)-epicatechin (1), quercetin-3-O-(2,6-di-α-l-rhamnopyranosyl)-β-d-galactopyranoside (2), 4′′-O-glucosylvitexin (3) and 2′′-O-rhamnosylvitexin (4) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Flavonoids are known for their high diversity, wide distribution, and multiple biological functions 32 . A previous study has shown that the leaves of D. officinale contained high contents of flavonoids and showed strong DPPH radical scavenging activities 30 , so that the leaves could be developed as antioxidant sources for medicinal and health food resources.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are known for their high diversity, wide distribution, and multiple biological functions 32 . A previous study has shown that the leaves of D. officinale contained high contents of flavonoids and showed strong DPPH radical scavenging activities 30 , so that the leaves could be developed as antioxidant sources for medicinal and health food resources.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
“…AP2-like transcription factors belong to the large plant-specific superfamily APETALA2 (AP2), which take part in various regulatory pathways and act in multiple stages and tissues during plant development 27 . Some members of the AP2 gene family could affect internode length, and the overexpression of an AP2-like gene in Arabidopsis promotes plant height 32,38 . Four unigenes expressed highly in stems and ten unigenes expressed highly in roots.…”
Section: Identification Of Degs In Stem Formation the Photoperiod Ofmentioning
confidence: 99%
“…The choice of the solvent system is critical in HSCCC. According to a previous study, the most suitable K value range for HSCCC is 0.5-2.0 [21]. If a proper solvent system is not selected, the separation time will be long, the separation efficiency will be low, and organic solvent usage will be high.…”
Section: Hsccc Separation Of Potential Lox and Ldh Inhibitors From Smentioning
confidence: 99%
“…DOPs have many pharmacological activities such as curving hypoglycemia [7], antioxidation [8], immunomodulation [9] and anti-tumor. Alkaloids of D. o cinale exhibit a variety of pharmacological activities such as antioxidant, anticancer, and neuroprotective activities [10], and avonoids of D. o cinale possess good functions on anti-cytotoxicity and antioxidant [11].…”
Section: Introductionmentioning
confidence: 99%